Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
y = 2x + 2
-4 = 2(-3) + 2
-4 = -6 + 2
-4 = -4
y = x - 1
-4 = -3 - 1
-4 = -4
It is the solution
Step-by-step explanation:
Answer: Yes, it is the solution to the system.
=========================================================
Explanation:
The point (-3,-4) means that x = -3 and y = -4 pair up together.
Let's plug those values into the first equation and simplify
y = 2x+2
-4 = 2(-3)+2 .... replace x with -3; replace y with -4
-4 = -6+2
-4 = -4 ... we get a true equation
Let's repeat for the other equation as well
y = x-1
-4 = -3-1
-4 = -4 .... this is also true
Since both equations are true, this means (-3,-4) is the solution to the system. The two lines intersect at (-3,-4).
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.